Organizing for Competitiveness – Structural and Process Characteristics of Organizational Design - Tomislav Hernaus; Ana Aleksic; Maja Klindzic (Contemporary Economics)
An emerging multidimensional approach to organizational design outlines the need for the alignment of relevant structural and process characteristics of organizations. However, neither the interaction of these characteristics nor their role and importance for organizational competitiveness is properly examined in the literature. Therefore, the main goal of this paper is to investigate the relationship between the structural and process characteristics of organizational design to determine how and to what extent these characteristics contribute to achieving a competitive advantage. The field survey was conducted on a cross-sectional sample of 134 Croatian companies. The research findings outlined the need for a new organizational design approach that emphasizes both the vertical and horizontal dimensions of design solutions. This paper contributes to previous research by showing that organizational design represents a source of competitive advantage only if structural and process characteristics are commonly designed. In addition, we confirmed that although structural characteristics are usually more often addressed, it is process characteristics that make a difference.